Variação da massa específica da madeira de Eucalyptus grandis aos 8 anos de idade em função de diferentes níveis de produtividade - De Rezende, M. A. [UNESP]; Saglietti, J. R C [UNESP]; Chaves, R. [UNESP] (My University, 1998)
It were analyzed Eucalyptus grandis trees of 8 years old in the forest group of Duraflora S/A, with different annual increments based on volume, to the related studies of specific gravity values based on productivity indexes. The methodology used in analysis of specific gravity was the gamma-ray attenuation technique of Americium-241. The Eucalyptus grandis showed a specific gravity decreasing with the increasing of parcel productivity. For a gain of 3,5 m3 in productivity there was a decreasing of 1% in specific gravity. Nevertheless, it was not observed correlation between specific gravity and basal area in a same parcel. The present work stands out too, some of the difficulties found with relation to wood specific gravity determinations and emphasize the importance of take samples in the form of full rounded plates in three or four relative positions in the tree.
Specific gravity variation of Eucalyptus grandis wood at 8 years old in function of a different productivity indexes
Keywords: Eucalyptus grandis; Specific gravity; Wood